Analisis Prosedur Pemberian Kredit Modal Kerja Pada Bank Sultra Cabang Utama Kendari - Alviana, Lana; kambolong, makmur; sahrun, sahrun (Business UHO: Jurnal Administrasi Bisnis, 2019)
This study aims to determine the procedure for granting working capital loans at the South Sulawesi Southeast Sulawesi Main Branch Bank. The informants in this study were bank employee informants and informants from borrowers of capital business funds. The number of informants in this study were 3 people, consisting of 2 South Sulawesi Bank Employees, and 1 South Sulawesi Bank working capital customer. Data collection techniques carried out by means of interviews, namely data collection conducted by conducting question and answer directly with the Chairman or with the Employees of PT. Bank Sultra Utama Kendari Branch, specifically regarding crediting and study of documents that is, collecting data through documents or archives in the object of research as well as covering the history of the establishment of the company, organizational structure, and other data provided by the company. The analysis technique used to analyze the problems raised in this study is to use quantitative and qualitative descriptive data analysis techniques, namely the systematic depiction or decomposition of the procedure for granting credit by PT. Bank Sultra Kendari Main Branch to prospective debtors.The results showed that the procedure for granting credit is the stages that must be passed before a credit is decided to be disbursed. The procedure for granting working capital loans, starting from prospects of customers who come for the purpose of applying for credit, then collected files and requests for prospective customers. After that the completeness of the file is checked, and if the file is considered complete, the disposition of the application is carried out in accordance with the Standard Operating Procedure (SOP). If the requirements are deemed complete and feasible, then the leadership will continue to be recommended, and if the recom- mendation is accepted, then the credit analyst and credit admin will continue to be issued a letter of credit approval and finally an agreement is reached on the credit agreement and binding of the notary deed